Thermal convection in rotating ferromagnetic liquid with thermorheological and magnetorheological effects - R. Prakash; Umair Khan; Fehmi Gamaoun; K. Sarada; K.V. Nagaraja; Harjot Singh Gill; Anuar Ishak; M. Modather M. Abdou; Ahmed M. Hassan (Case Studies in Thermal Engineering, 2024)
Rotational effects are investigated in Newtonian ferromagnetic liquids with linear stability modified by temperature and magnetic field. When thermorheological and magnetorheological effects are taken into account, the fluid's rheological behaviour becomes more complex. Thermorheological effects deal with viscosity changes in relation to temperature, whereas magnetorheological effects deal with viscosity changes in reaction to an applied magnetic field. Understanding the interplay between these effects and thermal convection sheds light on how connected these processes are. In idealized boundary conditions, the convective thresholds are expressed explicitly using the Galerkin technique. In the case of free-free and rigid upper-free boundaries, the exchange of stability principle is demonstrated, and corresponding results are presented. The oscillatory convection is not a preferable mode of instability for ferromagnetic liquids with Prandtl numbers more than one. In addition, rotational and ferromagnetic parameters are discussed in relation to system instability. Results reveals that an increase in Taylor number has a stabilizing effect on the system. Increasing magnetic buoyancy number, results in destabilizing effects on the system. Ferroconvection is not affected due to the nonlinearity of non-magnetic parameter. The results obtained agree truly with those of limiting cases.